Rapid review of gender-affirming healthcare for children and adolescents: Evidence synthesis (2021–2025) and recommendations for South Africa - Ingrid Lynch; KL Dunkle; Chris McLachlan; Pierre Brouard; Landa Mabenge; Sakhile Msweli; Liberty Matthyse; Marion Stevens; Robin Dyers; Jenna-Lee de Beer-Procter; Kevin Adams; W.D. Francois Venter; et al. (Southern African Journal of HIV Medicine, 2026)
Background: Since the publication of the Southern African HIV Clinicians Society Gender-Affirming Healthcare (GAHC) Guideline in 2021, global evidence on care for transgender and gender-diverse (TGD) youth has expanded. An updated, locally grounded, evidence-informed assessment of health outcomes can support South African stakeholders, particularly as both adolescents and TGD persons are populations of relevance to HIV prevention, sexual health, and integrated healthcare programmes in South Africa. Objectives: To synthesise global empirical evidence (2021–2025) across psychosocial, endocrine, surgical, policy, and non-medical gender-affirming interventions for TGD youth under 18, with attention to South Africa’s social, legal, and health-system, and HIV-service delivery context. Method: A rapid review was conducted across 12 databases, supplemented by targeted searches for recent systematic reviews. Eligible sources comprised peer-reviewed empirical studies (N ≥ 5) reporting psychosocial or physical health outcomes of relevant interventions for TGD youth under 18 (or their families), and systematic or grey-literature reviews with reproducible methods. Findings were synthesised narratively by intervention domain. Results: The review included 200 primary studies, 29 academic systematic reviews, and four grey-literature reviews. Affirming psychosocial interventions were associated with reduced distress, anxiety and suicidality, and improved functioning and belonging. Puberty blockers and hormone therapy produced expected physiological outcomes under specialist care, with generally mild adverse events and stable or improved mental health. Restrictive policies were linked to poorer mental health, while protective policies improved outcomes. Most studies were small, observational, and Global North-focused. Conclusion: Evidence supports the safety and effectiveness of GAHC for TGD youth. Strengthening affirming care, timely clinical access, and protective policies in South Africa may improve healthcare engagement and support the delivery of integrated adolescent, sexual health, and HIV-related services for TGD youth.